Inter-sectorial network for assisting women in situations of violence: handicraft work built by the people - Laura Ferreira Cortes; Stela Maris de Mello Padoin; Jaqueline Arboit (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to discuss the meanings attributed by professionals to the construction of the service network for women in situations of violence. Methods: Convergent Care Research developed with the application of a convergence group with 32 participants from the health, social assistance, or public security sectors, in Santa Maria, Rio Grande do Sul. The data was produced during ten meetings, based on the problematization methodology, and submitted to analysis of thematic content and interpreted with the referential of networks. Results: the construction of the network is an artisanal work carried out by people continuously, permeated by bonds, communication and partnerships between services and knowledge of work processes. Lashings require permanent movement. Final Considerations: building a network implies defining intertwining lines; form nodes that create cross-sector connections. There is a need to institutionalize processes through care continuity protocols, associated with an efficient communication system between sectors.